A new educational software package for photovoltaic system feasibility: PVGUI - Bilu, Ayse C.; Durusu, Ali; Dogansahin, Kadir; Kekezoglu, Bedri (SAGE PUBLICATIONS LTD, 2019)
With the increase in the market share of renewable energy sources, the feasibility analysis of the renewable energy-based power systems has also gained importance. In this study, a MATLAB-based interface for the feasibility analysis of photovoltaic systems is proposed in order to be used in educational purposes. The interface has been presented to the students of Yildiz Technical University as an educational material, and positive feedback has been received from the majority of the students.
Keywords: Photovoltaic system; feasibility analysis; MATLAB; GUI; Education & Educational Research; Engineering